Long-Term Outcome of Endonasal Endoscopic Skull Base Reconstruction with Nasal Turbinate Graft - El-Banhawy, Omar A; Halaka, Ahmed N; Altuwaijri, Mohammed A; Ayad, Heshmat; El-Sharnoby, Mohamed M (Skull Base, 2008)
Objective: To study the long-term outcome of endonasal endoscopic skull base reconstruction with nasal turbinate tissue free graft. Patients and Methods: This study included 55 consecutive patients who underwent endonasal endoscopic skull base reconstruction with nasal turbinate graft and were available for follow-up. They were 30 patients with pituitary adenomas, 20 with cerebrospinal fluid (CSF) rhinorrhea of different etiologies, three with meningoencephalocele, and two with skull base meningiomas. Autologous nasal turbinate tissue materials were used in reconstructing the skull base defect. Clinical follow-up with endoscopic nasal examination was done routinely 1, 3, 6, and 12 months after surgery. Computed tomography and magnetic resonance imaging were performed when indicated. The follow-up period ranged from 6 months to 8 years. Results: There were no major operative or postoperative complications. Nasal turbinate graft was effective in sealing of intraoperative CSF leak, obliteration of dead space, and anatomic reconstruction of the skull base. There was no evidence of graft migration or inflammatory changes. Starting from 3 months after surgery to the rest of the follow-up period, endonasal endoscopic view of the site of duraplasty showed that: with small skull base defect (less than 5 mm), there was neither dural pulsation nor prolapse; with moderate-sized defect (5 to 10 mm), there was dural pulsation without prolapse; with larger defect (> 10 mm), there was dural pulsation and prolapse. These finding were constant regardless of the etiology of the lesion and the reconstruction material used. Conclusions: This long-term study demonstrated the efficacy of nasal turbinate graft in sealing of CSF leak without any delayed complications. Other rigid materials may be considered in reconstruction of large skull base defect (more than 10 mm) to prevent dural prolapse and herniation. For any future endonasal procedure for those patients, who had previous endonasal endoscopic duraplasty, the surgeons should be fully aware of the state of duraplasty (e.g., dural prolapse) to avoid any intraoperative complication (e.g., penetration of the prolapsed dura during nasal packing).
Keywords: Endonasal; endoscopic; skull base; nasal turbinate